The analysis on the correlation parameters of the embankment compaction under in situ conditions - Kumor, Maciej; Kumor, Łukasz; Farmas, Joanna (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Geotechnical assessment of the implementation correctness of a road embankment wide range of issues, among which important selection and control of the quality of the earthworks are extremely significant. The article presents results of in situ tests determining correlations between the depending parameters defined by a static plate – VSS test – E1 and E2, and obtained from the study LFG Dynamic Load Plate. Studies indicate that the determination of the correlation between the parameters characterizing the particle size distribution (Cc, Cu, D10, D20, D30, D60), and the compaction parameters obtained by examining the compaction of sand embankment (Evd, E1, E2, I0) is physically complex and hence extremely difficult.